Child tracking system using smartphone - Taha A. Taha; Abadal-Salam T. Hussain; Hazry Desa; Faris Hassan Taha; Yasin Bektaş (Bulletin of Electrical Engineering and Informatics, 2023)
The number of missing children and kidnapping is on the rise in recent years. Every parent wills definitely going through an agonizing experience to have their children missing. Therefore, there are many safety measurements to prevent this incident from happening. The help of modern technologies is one of the ways to reduce children missing and kidnapping. A child can be tracked by using the global positioning system (GPS) and global system for mobile communication (GSM) technology. Advanced child monitoring systems are expensive. Not all families have the same living standards. For this purpose, a low-cost child tracking system is proposed in this study. The implementation of the proposed approach is reported in real-time.